Convenient and Scalable Synthesis of Aryldichlorophosphines and Primary Arylphosphines via Perthiophosphonic Anhydrides - Picthall, Daniel; Surgenor, Brian A.; Kilian, Petr (Synthesis, 2023)
A scalable synthetic route to both primary arylphosphines ArPH2 and aryldichlorophosphines ArPCl2 is reported. The C–P bond formation was performed in a highly regiospecific manner through electrophilic substitution of selected aromatic hydrocarbons (ArH) with phosphorus pentasulfide. The resultant perthiophosphonic anhydrides Ar2P2S4 were then reacted with LiAlH4 to give primary phosphines ArPH2. Subsequent reaction of ArPH2 with phosgene solution gives dichlorophosphines ArPCl2. Each reaction step requires minimum purification and uses commercially available and economical precursors. The scope of the reaction was shown to include alkoxy and phenoxy substituted benzenes as well as naphthalene and fluorene as starting materials.
Keywords: primary phosphine; chlorophosphine; organophosphorus synthesis; 31P NMR